2007
DOI: 10.1038/ng2097
|View full text |Cite
|
Sign up to set email alerts
|

A single positively selected West Nile viral mutation confers increased virogenesis in American crows

Abstract: West Nile virus (WNV), first recognized in North America in 1999, has been responsible for the largest arboviral epiornitic and epidemic of human encephalitis in recorded history. Despite the welldescribed epidemiological patterns of WNV in North America, the basis for the emergence of WNVassociated avian pathology, particularly in the American crow (AMCR) sentinel species, and the large scale of the North American epidemic and epiornitic is uncertain. We report here that the introduction of a T249P amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
292
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(304 citation statements)
references
References 29 publications
9
292
1
2
Order By: Relevance
“…Several examples of single-nucleotide polymorphisms having pronounced evolutionary consequences can be cited -e.g., in genes involved in pathogen virulence (Brault et al, 2007) or pigmentation (Nachman et al, 2003;Manceau et al, 2010). Because the positively selected sites in the MC1R identified in this study are located in critical regions of ligand binding of the protein, functional changes in these regions might have direct consequences for some phenotypes.…”
Section: Selection On Mc1rmentioning
confidence: 88%
“…Several examples of single-nucleotide polymorphisms having pronounced evolutionary consequences can be cited -e.g., in genes involved in pathogen virulence (Brault et al, 2007) or pigmentation (Nachman et al, 2003;Manceau et al, 2010). Because the positively selected sites in the MC1R identified in this study are located in critical regions of ligand binding of the protein, functional changes in these regions might have direct consequences for some phenotypes.…”
Section: Selection On Mc1rmentioning
confidence: 88%
“…Infectious clones of lineage 2, African strain B956 [26], lineage 1, American NY99 [1,3,30,36,43,50], and Australian Kunjin strains [8,40] have been generated and used to decipher the role of viral proteins in virulence [43,51], neuroinvasiveness [1,36] and escape from host defences [23,52], as well as to evaluate the impact of point mutations [23,53,54]. These tools have substantially facilitated identification of molecular determinants of WNV virulence, albeit in a non-European context.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus important to extend molecular studies of WNV to European strains, for which results have sometimes been at odds with those for the NY99 strain. Brault et al [54] identified a point mutation, T249P, in NS3, as playing an important role in the virulence of NY99 in American crows, while Sotelo et al [55] showed that a 2007 Spanish strain bore the same mutation but was much less virulent than the NY99 strain in mice. Clearly, comparison of molecular clones derived from different continents is indispensable for identifying the genetic differences underlying the different epidemiological patterns.…”
Section: Discussionmentioning
confidence: 99%
“…A mutation causing a single amino-acid substitution in the WNV genome generated a virus phenotype that was highly virulent to birds and particularly corvids (Brault et al, 2007). Compared to other bird species, corvids develop very high viral titers in blood and tissues, which contribute to pathology and death Reisen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%